Effectiveness of cocoa bean extract mouthwash against gingivitis in pregnant women in Aceh Besar - Nuraskin, Cut Aja; Reca; Mardiah, Ainun; Rahmayani, Liana (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Gingivitis and periodontitis are the most common dental support tissue problems in dentistry. Gingivitis is an inflammation of the gingiva due to the body’s response to the accumulation of dental plaque bacteria in the form of Streptococcus mutans, Streptococcus sanguis, Actinomyces, and Spirochaeta on the surface of the teeth. Gingivitis and nutritional status in pregnant women are related to the risk of 8.75 times the birth of low-birth-weight babies (BBLR) and premature babies. Prevention of gingivitis can be done chemically through gargling with antibacterial mouthwash. Therefore, herbal ingredients are needed that can prevent plaque and control gingivitis. This study aims to determine the effectiveness of mouthwash of cocoa bean extract against gingivitis. Methods: This study used the post-test only control group design method. The study was conducted on pregnant women in Bayu Aceh Besar village with a total of 30 samples. The sample was divided into 3 groups that received different treatments. Group 1 was instructed to do a mouthwash with cocoa extract mouthwash while Group 2 with chlorhexidine, group 3 with mineral water. Each pregnant woman gargles for 30 seconds (20 ml) for 3 days. Results: Analysis of the gingival index before and after using cocoa seed extract mouthwash showed that this mouthwash was more effective in reducing the gingival index with a value of p=0.012 (p<0.05). Conclusions: Gargling with cocoa bean extract is more effective in reducing gingivitis. We recommend further studies to investigate the potential of cocoa bean extract for use in mouthwashes.